Quantum gate teleportation, universal entanglers and connections with the number theory - Fernando Vasconcelos Mendes (2015)
The present thesis can be divided in three parts: 1) Quantum gate teleportation; 2) Numerical search of universal entanglers; 3) Connections between quantum information and number theory. Regarding the quantum gate teleportation, a separability criterion of normal matrices is used to find the analytical conditions of the preservation of separability under conjugation. That analytical condition allowed to find the general formula of an element of $mathbbC^{4}$ Clifford group, as well to understand the role of the basis of measurement in the quantum gate teleportation protocol. Considering the searching for universal entanglers, the same separability criterion of normal matrices was used as fitness function in a computational heuristics, in prder to find good candidates for universal entanglers in $mathbbC^{3} otimes mathbbC^{4}$ and $mathbbC^{4} otimes mathbbC^{4}$ Hilbert spaces. At last, in the connection of quantum information with the number theory, it is presented the study of the preparation and entanglement of several multi-qubit quantum states based in integer sequences, and the Riemannian quantum circuit, a quantum circuit whose eigenvalues are related to the zeros of the Riemann zeta function. The existence of such circuit proves that is always possible to construct a physical system related to a finite amount of zeros.